161k views
4 votes
Fill the table using this function rule
y=-10x+3

Fill the table using this function rule y=-10x+3-example-1

2 Answers

3 votes

Answer:

if x=-6 y =-10(-6)+3=60+3=63

and if x=-3, y= -10(-3)+3=30+3=33

then if x=0, y =-10(0)+3=0+3=3

finally if x=3 y=-10(3)+3=-30+3=27

Explanation:

you are to use the equation given to you, then you should be substituting the value of x in the equation i.e y=-10x+3

User Ryan Culpepper
by
4.9k points
3 votes

Hey there!

y=-2x+3

If x=-6

y=-2(-6)+3

y=12+3

y=15

y=-2(-3)+3

y=6+3

y=9

y=-2(0)+3

y=0+3

y=3

y=-2(3)+3

y=-6+3

y=-3

Hope this helps you! :)

~Just a depressed teen who loves Biology and Maths and misses her best friend


(:GraceRosalia :)

User Anna K
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.